Hepatitis C: pay now or pay later?. (December 2015) - Smyth, Dan; Webster, Duncan
Hepatitis C is a leading cause of liver disease and resulting complications are predicted to increase in the coming decades. However, recent availability of interferon-free treatment has put the spotlight on this epidemic and its health and economic impacts. Yet the cost of therapy is frequently prohibitive. When available, treatment provides an opportunity to abort disease progression, thus forgoing expensive downstream healthcare expenditures. Cost savings from therapy seem both probable and measurable in select patients with advanced disease and low risk of reinfection. The economic argument for early treatment is not as clear in those with less advanced liver disease and higher risk of reinfection. The optimal alignment of the relevant clinical and epidemiologic variables has yet to be clearly defined.